The upper thermal tolerance of the secondary screwworm, Cochliomyia macellaria Fabricius (Diptera: Calliphoridae). (October 2019) - Rusch, Travis W.; Adutwumwaah, Abena; Beebe, Lauren E.J.; Tomberlin, Jeffery K.; Tarone, Aaron M.
Abstract: Determining the thermal tolerance of an organism is important when assessing its activity time and survival rate in a given environment. However, thermal tolerance is not a static trait and may be influenced by a number of environmental and organismal factors. We report the results of three experiments investigating the effects of environmental temperature, exposure duration, age, sex, and nutrient availability on the upper thermal tolerance of the adult secondary screwworm, Cochliomyia macellaria . The probability of knockdown and survival was determined using a static method for different environmental temperatures (22, 40, 42, 44, or 45 °C), exposure durations (1, 2, 4, or 6 h), and nutrient availabilities (no food or water, water only, or both food and water) for both sexes and two age classes (young = 7–9 days post pupal emergence, old = 10–12 days post pupal emergence). In general, environmental temperature and exposure duration had the greatest effects on both the probability of knockdown and survival. As temperature or duration increased, the probability of knockdown increased while the probability of survival decreased. The availability of nutrients (water only or food and water) increased thermal tolerance at moderate temperatures (42 and 44 °C), but had no effect at 45 °C. Female flies were more thermally tolerant than males, regardless of nutrient availability. And age exhibited negligible effects on the probabilities of knockdown or survival, regardless of nutrient availability. These data show multiple environmental factors affected the thermal tolerance of C. macellaria . Thus, such aspects of basic thermal biology should feature more prominently in applied fields using blow flies, including but not limited to forensic entomology, disease ecology, and pollination ecology. Highlights: As temperatures increased the probability of knockdown increases while the probability of survival decreased. As exposure duration increased the probability of knockdown increases while the probability of survival decreased. Food and water produced a buffering effect at intermediate temperatures of 42 and 44°C, but had no effect at 45°C. Female Cochliomyia macellaria (Diptera: Calliphoridae) were more thermally tolerance than male C. macellaria .